2012
DOI: 10.1021/ja303883c
|View full text |Cite
|
Sign up to set email alerts
|

The Innate Immune Protein Nod2 Binds Directly to MDP, a Bacterial Cell Wall Fragment

Abstract: Mammalian Nod2 is an intracellular protein that is implicated in the innate immune response to the bacterial cell wall and is associated with the development of Crohn’s disease, Blau syndrome, and gastrointestinal cancers. Nod2 is required for an immune response to muramyl dipeptide (MDP), an immunostimulatory fragment of bacterial cell wall, but it is not known whether MDP binds directly to Nod2. We report the expression and purification of human Nod2 from insect cells. Using novel MDP self-assembled monolaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
196
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(204 citation statements)
references
References 31 publications
5
196
0
3
Order By: Relevance
“…Rather than refuting the importance of the LRRs, this observation may reflect a need for the nucleotide-binding domain to facilitate proper folding of the NOD2 LRRs. Simultaneously, surface plasmon resonance studies reported direct binding between NOD2 and MDP (Grimes et al, 2012). Confirming the need PRRs in Health and Disease for further studies to characterize the precise nature of the interaction of NOD2 with MDP, this work reported competitive binding, at nanomolar affinities, for both the agonist and antagonist stereoisomers of MDP with NOD2.…”
Section: Activation and Signal Transduction In The Nucleotide-bindsupporting
confidence: 72%
“…Rather than refuting the importance of the LRRs, this observation may reflect a need for the nucleotide-binding domain to facilitate proper folding of the NOD2 LRRs. Simultaneously, surface plasmon resonance studies reported direct binding between NOD2 and MDP (Grimes et al, 2012). Confirming the need PRRs in Health and Disease for further studies to characterize the precise nature of the interaction of NOD2 with MDP, this work reported competitive binding, at nanomolar affinities, for both the agonist and antagonist stereoisomers of MDP with NOD2.…”
Section: Activation and Signal Transduction In The Nucleotide-bindsupporting
confidence: 72%
“…In contrast, NOD2 recognizes MDP, a PGN fragment that is found in Gram-negative and Grampositive bacteria alike (34) ( Table 1). The LRR region of NOD1 or NOD2 is essential for PGN detection (33,106), and recent evidence has revealed direct binding of these domains to PGN fragments (37,62,77). It is thought that direct binding of MDP or ieDAP leads to a conformational change of the LRR horseshoe structure and to homodimerization of the NLR via the NOD domain (56, 100).…”
Section: Noncanonical Inflammasomes and Intracellular Lps Sensingmentioning
confidence: 99%
“…It is involved in the recognition of portions of muramyl dipeptide (MDP; Girardin et al, 2003;Grimes et al, 2012) constituent of the cell wall of Gram-positive and Gram-negative bacteria (Strober et al, 2006).…”
mentioning
confidence: 99%